If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9 + -6y) + 5y = 4 (9 * 2 + -6y * 2) + 5y = 4 (18 + -12y) + 5y = 4 Combine like terms: -12y + 5y = -7y 18 + -7y = 4 Solving 18 + -7y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -7y = 4 + -18 Combine like terms: 18 + -18 = 0 0 + -7y = 4 + -18 -7y = 4 + -18 Combine like terms: 4 + -18 = -14 -7y = -14 Divide each side by '-7'. y = 2 Simplifying y = 2
| 2b=7+3b | | 18-(5-x)= | | 3(2x-1)+5(x+2)=40 | | -71-26g=565 | | -3-5(6-3)= | | 13=w/2-16 | | (x+1)+(2x-10)= | | 0=-18-6y+2x | | 5y=-x+12 | | f(9)=4x+1 | | 31=5w-9 | | (x+1)-(2x-5)= | | 2x^3+9x^2-84x=0 | | F-7-2f-2-2f=0 | | 4y-2=8 | | (5+x)+(3x)+(x)=41 | | (7x^2/3)(6x^1/4 | | 12=3/2a | | 6-2(3x+2)=-22 | | 10z=50 | | 6x^2=21x-15 | | x^2+4y^2+4xy^2=0 | | x(x+3)(x+9)=400 | | -1x^2-4x-3=0 | | 64xsquared=25 | | 39(x-156)=78 | | 5x+9=23+x | | 5x-2(2x+4)=4x+(x+2) | | 4x+2x+3=21 | | 8x^2-50x-3y-15=0 | | -2sin^2x+sinx+1=0 | | 131/2(6X-4) |